Interaction of Normal and Sickle Hemoglobins for Sodium Dodecylsulphate and Hydrogen Peroxide at pH 5.0 and 7.2. (10th October 2013) - Ezebuo, Fortunatus C.; Eze, Sabinus Oscar O.; Lukong, Colin B.; Chilaka, Ferdinand C.
Abstract : Clinical manifestations of malaria primarily result from proliferation of the parasite within the hosts' erythrocytes. The malaria parasite digests hemoglobin within its digestive vacuole through a sequential metabolic process involving multiple proteases. The activities of these proteases could lead to the production of ROS which could lead to the death of the parasites due to the destruction of their membrane. The action of SDS on hemoglobins can be likened to the way malarial proteases destabilizes host hemoglobin. Hence, the study was designed to determine the binding parameters of SDS and H2 O2 for normal, sickle trait carrier and sickle hemoglobins at pH 5.0 and 7.2 using UV-VIS Titration Spectrophotometry. Hb-SDS interactions were significantly different at pH 5.0 but were not at pH 7.2. Also, Hb-H2 O2 interactions were statistically different at pH 5.0 and 7.2. The interactions suggest that HbA and HbS are easily destabilized than HbAS and that HbAS has more affinity for H2 O2 . These suggest a production of more ferryl intermediates or hydroxyl radicals. All these interactions may hinder the development of the malaria parasite at the intraerythrocytic stage and could likely account for a significant proportion of the mechanism that favours the resistance to malaria by individuals with HbAS.